TWITTERATURE: A TEXTUAL ANALYSIS OF THE COMPILATION OF IDEAS OR THE DISCONNECTION OF IT - R. Hariyani Susanti; Aramudin Aramudin; Welli Marlisa; Vera Sardila; Herlinda Herlinda (INOVISH JOURNAL, 2022)
Delivering ideas in a form of paragraphs, there are certain rules to follow for it to be accepted and easily understood by the targeted readers. However, with the rise of social media and the internet, there must be also changes in the world of language and literature. Some rules do not apply in this type of media, especially on Twitter. In 2012 Twivortiare, a novel consisting of a tweet compilation by Ika Natassa was released. This book is widely accepted by readers. In a text structure and text signal, this is very unusual. Using critical textual analysis the author finds out how ideas are being delivered in this type of literary work, whether it is disconnected or compiled. Through this analysis it is concluded that as long as the ideas are intact and can be understood by readers, twitterature is considered a literary work.